Strategi Komunikasi Dakwah Ustadz Asmar Habibie Dalam Membangun Relasi Dengan Jama’ah Di Era Digital - Latifah Aini; Nashrillah MG (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to identify and analyze how Ustadz Asmar Habibie designs a da'wah communication strategy in building relationships with the congregation in the digital era. The research method used in this study is a descriptive qualitative method using observation, interviews, and documentation, especially the analysis of Ustadz Asmar Habibie's da'wah video content on the Instagram and TikTok social media platforms. The results of this study indicate that the da'wah communication strategy used by Ustadz Asmar Habibie in building relationships in the digital era by utilizing digital media platforms, namely creating da'wah and social content on social media, also establishing close relationships with the congregation through replying to comments with funny vt and jokes that are his trademark. In this case, Ustadz Asmar Habibie can be widely known by young people and parents in absorbing religious values and he can reach wider relations both in West Pasaman, outside the district and even outside the province.